Global Liquidity Transmission to Emerging Market Economies, and Their Policy Responses - Choi, Woon.; Kang, Taesu; Kim, Geun-Young.; Lee, Byongju (Washington, D.C. : International Monetary Fund, 2017)
This paper distills and identifies global liquidity (GL) momenta from the macro-financial data of advanced economies through a factor model with sign restrictions as policy-driven, market-driven, and risk averseness factors. Using a panel factor-augmented VAR, we investigate responses of emerging market economies (EMEs) to GL shocks. A policy-driven liquidity increase boosts growth in EMEs, elevating stock prices and currency values, while a risk averseness rise has an opposite effect. A market-driven GL expansion boosts stock markets and lowers funding costs, promoting competitiveness and current account. Inflation targeting EMEs fare better than EMEs under alternative regimes with respect to macrofinancial volatility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet